2013
DOI: 10.1186/1471-2164-14-367
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and specific detection of mosaic chromosomal abnormalities using the Parent-of-Origin-based Detection (POD) method

Abstract: BackgroundMosaic somatic alterations are present in all multi-cellular organisms, but the physiological effects of low-level mosaicism are largely unknown. Most mosaic alterations remain undetectable with current analytical approaches, although the presence of such alterations is increasingly implicated as causative for disease.ResultsHere, we present the Parent-of-Origin-based Detection (POD) method for chromosomal abnormality detection in trio-based SNP microarray data. Our software implementation, triPOD, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…To get a rough sense of how well our 624 ''undetermined'' calls match the Machiela et al set in terms of chromosomal aggregation by copy number, we calculated the average LRR deviation per chromosome for these calls. The averages are consistent with the copy-number distribution by 12, and 15 showed the highest average LRR deviation for undetermined calls, whereas chromosomes 10, 13, and 20 showed the lowest average LRR deviation. Of note, chromosome 10 had the fewest calls (16), so sampling variation might explain its unexpected ranking.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…To get a rough sense of how well our 624 ''undetermined'' calls match the Machiela et al set in terms of chromosomal aggregation by copy number, we calculated the average LRR deviation per chromosome for these calls. The averages are consistent with the copy-number distribution by 12, and 15 showed the highest average LRR deviation for undetermined calls, whereas chromosomes 10, 13, and 20 showed the lowest average LRR deviation. Of note, chromosome 10 had the fewest calls (16), so sampling variation might explain its unexpected ranking.…”
supporting
confidence: 82%
“…Several reports have cited the potential increase in sensitivity from using haplotype information. 11,12 Below, we summarize the genomic locations of our discovered aberrations and describe characteristics of these aberrations in comparison to those discovered in a previous analysis of these data, and we report on the association between risk of mosaicism and age.…”
mentioning
confidence: 94%
“…These highly sensitive haplotype-based computational methods can deal with low-cellularity samples, or situations where the aberrant cell fraction is below 5% by assessing consistency between BAF values and inherited chromosomes, estimated statistically (138,139), capturing the direction of the BAF values (136,137,140,141). This extra level of specificity is critical when attempting to characterize phenomena that are rare (infrequent along the genome or in few samples) and/or subtle (occurring in a low proportion of the cells from which the DNA was obtained), settings anticipated in normal-appearing the airway field of injury or in preneoplasia.…”
Section: Identification Of Subtle Alterations In Lung Premalignancymentioning
confidence: 99%
“…APP and SUMO found to be decreased, and are involved in apoptosis[40]AGREBlood and lymphoblasts334 familiesReanalysis of data set using different analysis methodAssociation found in chromosome 1, which was previously overlooked. Further evidence that 17q11 is associated with ASD[191]AGREGenomic data12 familiesMethod paperDescription of parent of origin method to detect mosaic chromosomal abnormalities.[192]AGREBlood and lymphoblasts518 familiesReplication study and functional studyThe gene EN2 suggested to act as ASD susceptibility locus, and mutations could alter brain development[41]AGREBlood and lymphoblasts389 families (AGRE) 518 families (total)Association studyHaplotypes found in ASD families found to affect regulation of EN2 gene expression[75]AGREBlood and lymphoblasts954 subjectsGene-gene interaction studyGlutathione pathway is implicated in autism[28]AGREBlood and lymphoblasts6056 subjects (TOTAL)4444 subjects (AGRE)GWAS UBE3A, NRXN1, BZRAP , and MDGA2 found to have disruptive CNVs amongst ASD patients, some only occurring once amongst patients[83]AGREGenomic data830 subjectsMethods paperUse of disease symptoms improves detection of linkage in genetic data. Useful when heterogeneity is involved[38]AGREBlood18 subjectsGenotype-phenotype study3 out of 18 patients with ASD and macrocephaly had mutations in PTEN gene.…”
Section: Resultsmentioning
confidence: 99%